2018
DOI: 10.1021/acs.cgd.8b00394
|View full text |Cite
|
Sign up to set email alerts
|

Size and Morphology Controlled Synthesis of Boehmite Nanoplates and Crystal Growth Mechanisms

Abstract: The aluminum oxyhydroxide boehmite is an important crystalline phase in nature and industry. We report development of a flexible additive-free hydrothermal synthesis method to prepare high quality boehmite nanoplates with sizes ranging from under 20 nm to 5 μm via using hydrated alumina gels and aluminum hydroxide amorphous powders as precursors. The size and morphology of the boehmite nanoplates was systematically varied between hexagonal and rhombic by adjusting precursor concentrations, pH, and the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 62 publications
(109 reference statements)
7
93
1
Order By: Relevance
“…The XRD pattern of the boehmite@tryptophan‐Pd nanocatalyst is shown in Figure . The peaks at 2 θ values of 14.01°, 18.54°, 20.13°, 24.95°, 28.95°, 41.45°, 47.25°, 53.24°, 55.22°, 59.12°, 64.24° and 68.26° are related to (0 2 0), (1 2 0), (0 3 1), (1 3 1), (0 5 1), (2 0 0), (1 5 1), (0 8 0), (2 3 1), (0 0 2), (1 7 1) and (2 5 1) reflections, respectively, which are in agreement with the standard boehmite XRD pattern . More importantly, the phase of boehmite is not destroyed during the modifications.…”
Section: Resultsmentioning
confidence: 98%
“…The XRD pattern of the boehmite@tryptophan‐Pd nanocatalyst is shown in Figure . The peaks at 2 θ values of 14.01°, 18.54°, 20.13°, 24.95°, 28.95°, 41.45°, 47.25°, 53.24°, 55.22°, 59.12°, 64.24° and 68.26° are related to (0 2 0), (1 2 0), (0 3 1), (1 3 1), (0 5 1), (2 0 0), (1 5 1), (0 8 0), (2 3 1), (0 0 2), (1 7 1) and (2 5 1) reflections, respectively, which are in agreement with the standard boehmite XRD pattern . More importantly, the phase of boehmite is not destroyed during the modifications.…”
Section: Resultsmentioning
confidence: 98%
“…It was suggested that boehmite is produced via the reaction of aluminum ions migrating from the metal, reacting with hydroxyl ions and precipitating back onto the substrate [29]. More recent studies have demonstrated that the size and morphology of crystals can be controlled by variation of precursors, synthesis temperature, time, and pH value [32,33].…”
Section: Methodsmentioning
confidence: 99%
“…Various methods for preparing aluminum oxide hydroxide nanocrystals which can be dispersed in aqueous conditions have been reported. [23][24][25] It is expected that PMSQ-composite porous monoliths with various structures and properties can be prepared using the synthesis method reported in this paper.…”
Section: Formation Mechanism Of Pbnr-pmsq Structurementioning
confidence: 99%